The role of agriculture in the fast-growing Rwandan economy: Assessing growth alternatives - Diao, Xinshen; Bahiigwa, Godfrey; Pradesha, Angga (International Food Policy Research Institute, 2014)
This study assesses the future growth prospects of Rwanda. The report first focuses on broad economic growth using a rather aggregated 18-sector dynamic general equilibrium model to display the trade-off between rapid growth and structural change. The analysis shows that with the current investment pattern, rapid growth is possible but structural transformation is slow. With an overvalued exchange rate, growth in the tradable sector slows down and its share in the economy stays small. The importance of agriculture thus should be considered in the broad development strategy, for its role not only in poverty reduction but also in economic growth.